The Effectiveness of Mixing Herbicides and Manual Weed Control on Corn (Zea mays L) - Baidhawi, Baidhawi (Faculty of Agriculture, Universitas Malikussaleh, 2023)
Field trials were conducted in Januay 2021 cropping seasons to evaluate some herbicide mixtures and manual weed control method in the maize production. The experiment consisted of 10 treatments as follows: Metolachlor + atrazine (1.0 + 2.0 kg a.i./ha), metolachlor + atrazine (2.0 + 2.5 kg a.i./ha), metolachlor + atrazine (3.0 + 3.0 kg a.i./ha), pendimethlin + atrazine ( 1.0 + 2.0 kg a.i./ha), pendimethlin + atrazine (2.0 + 2.5 kg a.i./ha), pendimethlin + atrazine (3.0 + 3.0 kg a.i./ha), metolachlor + atrazine (1.0 + 2.0 kg a.i./ha) plus one supplementary hoe weeding (SHW) at 6 weeks after sowing (WAS) and pendimethlin + atrazine (1.0 + 2.0 kg a.i./ha) plus one SHW at 6 WAS, hand weeding at 3 and 6 WAS and a weedy check. These treatments used in randomized complete block design with three replicates. The rsults showed that metolachlor + atrazine and pendimethalin + atrazine at 1.0 + 2.0 kg a.i./ha plus one SHW at 6 WAS significantly reduced weed infestation and gave higher maize grain yield and economic returns. These methods are therefore recommended to farmers as alternative to two hand weeding at 3 and 6 WAS.